Inequality trends in Sweden 1978 - 2004 - David Domeij; Martin Flodén (Stockholm School of Economics, The Economic Research Institute (EFI), 2009)
We document a clear increase in Swedish earnings inequality in the early 1990s. Inequality in disposable income and earnings net of taxes and transfers also increased, but much less than the increased inequality in pre-government earnings. These different developments are most likely explained by the generous Swedish welfare system. Consistent with these observations, we see no clear trend in consumption inequality. We also estimate stochastic processes for household earnings. A simple random-walk process captures much of the life-cycle dynamics. But we find clear evidence that the true earnings process is not a random walk. We demonstrate that some estimation methods result in severe upward bias in the estimated volatility of permanent shocks if serial correlation in temporary shocks is ignored. Our estimation results show that the increase in earnings inequality is almost entirely driven by an increase in residual earnings inequality. Moreover, this increase was mostly generated by an increased volatility of persistent shocks.
Keywords: D31; D33; E24; J31; 330; income inequality; consumption inequality; stochastic earnings process; Einkommensverteilung; Lohnstruktur; Haushaltseinkommen; Soziale Ungleichheit; Verbraucherausgaben; Funktionelle Einkommensverteilung; Lebenszyklus; Schweden